Propolis Supplementation on Broiler Chicken Performances, Nutrient Digestibility, and Carcass Characteristics: A Meta-Analysis - Sadarman; A. Irawan; C. Hidayat; Elfawati; M. M. Sholikin; R. P. Harahap; R. K. Rusli; R. Solfaine; A. Sofyan; Nahrowi; A. Jayanegara (Tropical Animal Science Journal, 2021)
This meta-analysis was conducted to investigate the effect of dietary propolis supplementation on broiler performance, carcass characteristics, and nutrient digestibility evaluated at the starter and finisher phases. An online literature search was conducted using scientific platforms of Science Direct, PubMed, and Google Scholar to identify the studies utilizing propolis as dietary supplementation in broiler chickens. A total of 39 publications comprising of 58 experiments met the inclusion criteria. A mixed model procedure for meta-analysis was performed, considering the studies as a random effect and levels of propolis as a fixed effect. Regression analysis suggested that average daily gain (ADG), body weight, and average daily feed intake (ADFI) at starter and finisher phases were quadratically affected by supplementing propolis in the diet (p<0.01). Propolis also lowered the feed conversion ratio (FCR) throughout the periods (p<0.05). In addition, a positive effect of propolis inclusion was also observed on breast meat percentage (p<0.05). However, there was a negative linear relationship between propolis and the digestibility of dry matter (DMD) and organic matter (OMD) (p<0.01) at the starter period. Conversely, there was a linear increase in DMD (p<0.05) and a tendency to improve apparent metabolizable energy (AME) and phosphorus digestibility at the finisher period (p<0.10). Overall, it can be concluded that dietary propolis supplementation promoted better growth performance and feed efficiency when given at ~1.66-2.13 g/kg diets for starter and finisher phases in the broiler chickens. The effect of propolis on nutrient digestibility was positive at the finisher phase while it was detrimental at the starter phase.